P4.6 GREATER CAROTID CIRCUMFERENTIAL WALL STRESS IS ASSOCIATED WITH INCIDENT CARDIOVASCULAR DISEASE IN INDIVIDUALS WITH TYPE 2 DIABETES – THE HOORN STUDY - Veronica Onete*; Ronald Henry; Miranda Schram; Jacqueline Dekker; Giel Nijpels; Coen Stehouwer (Artery Research, 2015)
Introduction: Arterial remodeling is an adaptive phenomenon aimed at maintaining circumferential wall stress (CWS) within operating limits. It is characterized by widening of the inter-adventitial diameter (IAD) and increases in intima-media thickness (IMT). This process is maladaptive when CWS increases despite remodeling. Type 2 Diabetes (T2D) is associated with increased carotid CWS, but its association with cardiovascular disease (CVD) is unknown. Methods: The cohort consisted of 277 individuals with normal glucose metabolism (NGM), 162 with impaired glucose metabolism (IGM) and 131 with T2D (age 69.6 ± 6.4, 51.0% women, systolic pressure 141.9 ± 20.6 mmHg, bmi 26.9 ± 3.5 kg/m2, prior CVD 50.1%). Carotid arterial properties (IAD, IMT, lumen diameter (LD)) were quantified by ultrasonography. CWS was calculated as PP·LD/(2IMT), where PP is the brachial pulse pressure. A morbidity and mortality register was kept on all individuals. Results: After a median of 7.7 [IQR 7.0-8.1] years of follow up, 130 CVD events and 93 deaths were recorded. CWS was 31.7, 31.5 and 34.4 kPa in NGM, IGM and T2D, respectively (Ptrend= 0.06). Greater CWS was associated with incident CVD in T2D only (hazard ratio(95%CI) per SD increase in CWS for NGM: 0.92 (0.70–1.21); IGM: 1.02 (0.66–1.58) and T2D 1.52 (1.09–2.14), after adjustment for age, sex, height and other CVD risk factors.. No associations were observed between CWS and all-cause mortality. Conclusion: T2D is associated with greater CWS compared to NGM and IGM. Greater carotid CWS is associated with incident CVD in T2D but not in NGM or IGM.